DELAPAN BELAS TAHUN PERKEMBANGAN PENELITIAN SUSTAINABILITY REPORT: STUDI LITERATUR REVIEW - Bima, Muhammad; Indah Setiawan, Rhisma; Apriliana Agustin, Dwi; Djasuli, Mohamad (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
This study aims to examine the development of research related to sustainability report in the international scope. The review is based on 59 articles that discuss published in Scopus indexed scientific journals (Q1 and Q2). Articles were selected with the keyword